Transformation of Dittipidkor towards the Police Corruption Eradication Corps: An Urgency - Rizky Adhi Wigrhananto; Chairul Muriman Setyabudi; Iza Fadri (Transpublika Publisher, 2025)
This research aims to analyze the role of the Directorate of Corruption Crimes (Dittipidkor) Bareskrim Polri in combating corruption in Indonesia, examine the urgency of developing the organization into the Police Corruption Eradication Corps (Kortastipidkor), and identify factors considered in the development process. Corruption problems that are complex, massive, and involve various sectors require a more structured, focused and responsive handling. In this context, Dittipidkor Polri has a central role as the executor of law enforcement in synergy with other institutions such as the Corruption Eradication Commission and the Attorney General's Office. This research uses a qualitative approach with a field study method, through in-depth interviews with key informants such as the Head of the Renmin Subdivision of Dittipidkor and the Head of the Lempus Stamarena Polri, as well as analysis of legal and regulatory documents. This type of research is police management administration, with qualitative descriptive analysis techniques using the data triangulation method. The results showed that Dittipidkor plays a vital role in investigating corruption cases, but is hampered by various structural and resource constraints. Therefore, the transformation into Kortastipidkor is considered urgent to strengthen the effectiveness, professionalism and independence of handling corruption. Factors considered in organizational development include the legal basis, the need for structural reform, increasing HR competence, strengthening technology, and cross-agency coordination. With this transformation, it is hoped that Polri will be able to play a more strategic, responsive and accountable role in combating corruption in Indonesia.